2018
DOI: 10.1159/000487228
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Lens Dislocation after Cataract Surgery in Tambolaka, Southwest Sumba, Indonesia: A Case Report

Abstract: Intraocular lens (IOL) dislocation is a rare complication of cataract extraction requiring prompt surgery. This case report aims to raise awareness of such cases and the importance of post-surgery follow-up. A 58-year-old female patient was found with anterior IOL dislocation a week after phacoemulsification surgery in her right eye. Visual acuity of the right eye was 1/60 with ciliary injection and IOL dislocation to the anterior chamber of the right eye. The patient underwent surgery of the right eye and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…[ 6 ] The incidence of IOL dislocation within the first week after operation is 0.2–2.8%. [ 5 ] However, in our study, 36.04% of re-surgeries were for IOL repositioning, that is, 0.6% of total MSICS performed. Our results were consistent with a study by Greenberg et al ,[ 12 ] in which 0.9% of patients presented with IOL dislocation or underwent IOL exchange in a 90-day postoperative period.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…[ 6 ] The incidence of IOL dislocation within the first week after operation is 0.2–2.8%. [ 5 ] However, in our study, 36.04% of re-surgeries were for IOL repositioning, that is, 0.6% of total MSICS performed. Our results were consistent with a study by Greenberg et al ,[ 12 ] in which 0.9% of patients presented with IOL dislocation or underwent IOL exchange in a 90-day postoperative period.…”
Section: Discussionmentioning
confidence: 57%
“…IOL dislocation is one of the complications after cataract surgery that may occur after a few days to months. [ 5 ] Repositioning a dislocated PCIOL is the preferred option for many surgeons in achieving optimal visual recovery for the patient. [ 6 ] The incidence of IOL dislocation within the first week after operation is 0.2–2.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraocular lens (IOL)dislocation is one of the complications after cataract extraction with intraocular lens implantation. Although occurring rarely, it seriously affects the vision of patients 4 . A recent observational study showed that the cumulative IOL dislocation risk at 5,10,15,20,and 25 years after cataract extraction was 0.1%,0.1%,0.2%,0.7%,and 1.7%, respectively 5 .…”
Section: Discussionmentioning
confidence: 99%